Invasive lobular carcinoma of the breast with colonic metastasis: a case series of three patients - Shinya Otsuka; Kazuteru Komuro; Masato Suzuoki; Shuhei Hayasaka; Momoko Tsuda; Kimitoshi Kubo; Tomone Ueki; Yumi Moriya; Noriko Kimura; Masanori Ohara (Surgical Case Reports)
Abstract Background Although metastatic spread of breast cancer to the gastrointestinal tract is very rare, it is more likely to occur in invasive lobular carcinoma (ILC) than in ductal carcinoma. Colonic metastasis is particularly rare, and the treatment strategies for these cases are not clearly defined. Herein, we report three cases of ILC with various abdominal symptoms associated with colonic metastasis. Case presentation Case 1 A 70-year-old female patient with vomiting and melena was referred to our hospital. Endoscopic examination revealed a Dieulafoy ulcer in the rectum and an elevated lesion in the descending colon. She also had two breast nodules, and was diagnosed as ILC with colonic metastasis. Considering her general condition, the best supportive care (BSC) was offered. The patient died 4 months after confirmation of the diagnosis. Case 2 An 80-year-old female patient presented with diarrhea and vomiting. She was diagnosed with ILC with colonic metastasis, and a coloscopy revealed stenosis of the transverse colon with a metastatic lesion. Ileosigmoid bypass surgery was performed for intestinal obstruction, and systemic treatment for breast cancer was initiated. The patient developed peritoneal carcinomatosis and died 1 year and 2 months after surgery. Case 3 A 56-year-old female patient underwent left total mastectomy for ILC, and laparoscopic transverse colectomy was conducted for a colonic lesion 9 years and 2 months after. The diagnosis as colonic metastasis was not confirmed at that time. Two years and 2 months later, torose lesions were detected in the hepatic flexural and descending colon, and histopathological findings indicated that all colon tumors, including the previously resected tumor, were metastatic spread of ILC. Systemic treatment was continued, but the transverse colonic lesion penetrated the abdominal wall, and an abscess formed 2 years and 11 months after the resection. The fistula improved by continuous suction drainage following ileostomy but recurred, and the patient died 3 years and 8 months after colectomy. Conclusions Colonic metastases from breast cancer can trigger various abdominal symptoms, and the prognosis in these cases is generally poor. In selected cases, surgical treatment for abdominal symptoms and subsequent systemic therapy can contribute to a prolonged prognosis.